Enological potential of grapes produced in different periods in a tropical region of Northeast Brazil. - PEREIRA, G. E. (2010)
The lower-middle São Francisco river Valley is a new viticultural region located in northeast Brazil, between 8° and 90 Slatitude. ln this region it is possible to have two-three harvests a year, mainly due to an annual average temperature of 26.4°C, with about 567 mm of rainfall between Decem- berto March plus supplemental drip irrigation and altitude of 350m above sea leveI. A continuous vegetative development and grapevine growth occurs throughout the whole year. Grape composition can vary strongly according to harvest time of the year due to different c1imatic conditions.